Production and Chemical Characterization of Biochar–Fly Ash Enriched Compost for Tropical Acid Soil Ameliorant - Herdhata Agusta (JOURNAL OF TROPICAL SOILS, 2026)
Pineapple cultivation systems are produced in large quantities but are not optimally utilized. One widely used source of organic matter is compost. Biochar has received considerable attention as a functional amendment in the composting system. In addition to biochar, fly ash – a byproduct of coal combustion in thermal power plants – has emerged as a potential mineral additive for composting systems. The evaluation included temperature dynamics during production, moisture content, pH, N-total, C/N ratio, and macronutrient content at a predetermined observation time. The trial was structured using a single-factor Group Random Design with seven formulas and four replicates. Treatments A, B, and C are made by mixing biochar and FA into compost raw materials at the beginning of the composting process, with a composition of 75% compost raw materials + 20% biochar + 5% FA, 75% compost raw materials + 12.5% biochar + 12.5% FA, and 75% compost raw materials + 5% biochar + 20% FA. Treatment D consists of 100% compost raw materials without the addition of biochar and FA. Meanwhile,  the E, F, and G treatments are made by mixing biochar and FA into mature compost, with a composition of 75% compost + 20% biochar + 5% FA, 75% compost + 12.5% biochar + 12.5% FA, and 75% compost + 5% biochar + 20% FA. The treatment of 75% compostable raw materials, 5% biochar, and 20% fly ash at the beginning of the composting process shows the greatest potential balance, combining early enrichment with a high macronutrient content, an appropriate pH, and a final C/N ratio.